Self-Control as The Key to Good Manners: Building The Character of The Alpha Generation in The Digital Age - Fitria, Dian; Sumardjoko, Bambang (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to determine the effect of self-control on the manners of Generation Alpha among high school students in Karanganyar Regency who live in a digital environment with high technology exposure.Methodology: This study uses a quantitative descriptive method with a correlational design, with a proportional random sampling technique from a population of 3,649 students and involving 251 respondents who meet the age criteria of Generation Alpha. The research instrument is a 45-item questionnaire that has passed the validity test (r > 0.267) and has strong reliability (Cronbach's Alpha > 0.60). Data analysis was carried out using classical assumption tests for normality, multicollinearity, and heteroscedasticity, and hypothesis testing via simple regression and t-tests.Results: The results show that self-control has a positive and significant effect on the manners of Generation Alpha, evidenced by a Sig. value of 0.001 (<0.05) and a t-count of 5.607 > t-table of 1.970 so that H0 is rejected and H1 is accepted. The regression coefficient of 0.882 indicates that increased self-control directly contributes to improved manners, such as maintaining ethical communication, being humble, speaking well, and respecting others.Applications/Originality/Value: This finding confirms that self-control is a crucial factor in shaping polite behavior, especially in the context of digital life, which is vulnerable to negative impulses. Theoretically, this study strengthens the concept of self-control as a predictor of prosocial behavior, while practically offering important implications for schools, parents, and policymakers in designing character education interventions that focus on strengthening self-regulation to maintain polite values among Generation Alpha.